2014
DOI: 10.1155/2014/513460
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile and Correlation to Cardiac Risk Factors and Cardiovascular Function in Type 1 Adolescent Diabetics from a Developing Country

Abstract: Objective. The adverse role of dyslipidemia in predicting cardiovascular outcomes has not been elucidated extensively among type 1 diabetics in the literature. Methods. We assessed dyslipidemia and its correlation to other cardiac risk factors in adolescents with type 1 diabetes. Total thirty type 1 adolescent diabetics were evaluated for their metabolic profile, including serum lipids and echocardiography was performed. Results. The average age of the cohort was 14.3 ± 3.09 yr with disease duration of 5.35 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(62 reference statements)
1
15
0
1
Order By: Relevance
“…Other investigators nonetheless, have reported a significant association between CIMT and age, sex, smoking, blood pressure, body mass index [ 38 40 ] and the presence of diabetes or glucose intolerance [ 34 , 41 , 42 ]. In our study, like the findings of two other research groups [ 36 , 37 ], we did not observe a significant correlation between CIMT and gender, hyperlipidemia, hypertension, obesity, or HbA1c. However, we found just a significant association between age and duration of diabetes in poor glycemic group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other investigators nonetheless, have reported a significant association between CIMT and age, sex, smoking, blood pressure, body mass index [ 38 40 ] and the presence of diabetes or glucose intolerance [ 34 , 41 , 42 ]. In our study, like the findings of two other research groups [ 36 , 37 ], we did not observe a significant correlation between CIMT and gender, hyperlipidemia, hypertension, obesity, or HbA1c. However, we found just a significant association between age and duration of diabetes in poor glycemic group.…”
Section: Discussionsupporting
confidence: 87%
“…There are various reports in the literature regarding the association of CIMT with risk factors of carotid atherosclerosis. Some authors [ 36 , 37 ] were unable to find a statistically significant correlation between CIMT and CVD risk factors in diabetic patients. Other investigators nonetheless, have reported a significant association between CIMT and age, sex, smoking, blood pressure, body mass index [ 38 40 ] and the presence of diabetes or glucose intolerance [ 34 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados reforçam a importância de práticas alimentares saudáveis para reduzir o risco de doenças cardiovasculares (DCV) na idade adulta, uma vez que evidências sugerem que níveis elevados de lipídios séricos estão relacionados com maior incidência de hiperlipidemia, hipertensão e doença aterosclerótica 28 .…”
Section: Resultsunclassified
“…Marked dyslipidaemia is more characteristic for type 2 diabetes, and in T1DM lipid disturbances are rather mild [ 17 ]. However in both types of diabetes, poor glycemic control increases serum triglyceride levels and decreases HDL.…”
Section: Discussionmentioning
confidence: 99%